MODERNISATION OF THE CONTENT AND METHODS OF VOCATIONAL GUIDANCE FOR STUDENTS OF VOCATIONAL (VOCATIONAL AND TECHNICAL) EDUCATION (Innovative professional education, 2025)
The article considers some issues of modernization and expansion of professional orientation activities for vocational education applicants, which are of paramount importance for the restructuring of the economy in order to increase the defense capability of Ukraine under martial law
Keywords: Economic restructuring, modernization of content and methods, professional orientation, defense capability